Development of table tennis coaching : beginners - Belli, Taisa; Galatti, Larissa Rafaela (2021)
This document “Development of Table Tennis Coaching: Begginers”, represents a joint effort of the Brazilian Table Tennis Confederation (CBTM) and the School of Applied Sciences – University of Campinas (FCA-Unicamp), with Taisa Belli (PhD) and Larissa Rafaela Galatti (PhD) as authors. It represents the descriptive material of the Begginers Course, which is part of the Coach Education Program - CBTM, showing the integrated scope of Olympic and Paralympic Table Tennis.